Déjouer le spectacle de la violence. Représenter les événements du 11 septembre 2001 - Bertrand GERVAIS (E-REA)
Eluding the spectacle of violence. Representing the 9/11 events.How can we represent the 9/11 terrorist attack without fueling the spectacle that has already been framed? How can we go beyond the images already set, and propose a discourse and a representation that overcome the mere repetition? Instead of encouraging the exacerbation of representations that respect the logic of the spectacular, we must seek to delete the “towers” or, more precisely, to place them within a dialectic between presence and absence, transparency and opacity, simplicity and complexity. This is exactly what Art Spiegelman readilyunderstood. The 24 September 2001 issue of the New Yorker magazine, the first after the events of September 11, bore, on its front page, an image of a rare intensity. The image drawn by Spiegelman was monochrome, the two towers of the World Trade Center depicted in black on a black background. Their contour and shape could be perceived due to a slight depression on the surface of the paper. Reproduced on the cover of In the Shadow of No Towers (2004), this image offered a minimalist version of the attacks, relying on the elimination of color and the limits of figuration. We must look at the picture carefully to notice the towers. Michal Kosakowski gives a complementary strategy of this erasure in his film Just Like the Movies. His 21 minutes film is an extraordinary example of "found footage," which brings together excerpts from Hollywood films, more precisely Hollywood blockbusters and disaster movies. Dating from a pre-September 11 era, the films he has chosen and whose segments he has sewed together show beyond any doubt the eerie prefiguration in American imagination of the events of that day. In Just Like in the Movies, as in Spiegelman’s In the Shadow of No Towers, the towers are present but on the mode of absence, loss and denial. It is a hollow spectacle that is offered. We do not see the towers collapsing, or the airplanes hitting them, but these events are signified by an incredible cinematic device that transforms the events of that tragic day into a true figure, a complex sign that we must appropriate. We are led to project our own version of these events, through our memories and experience of that day. The film presents the events as a figure, both present and absent, a figure that asks us to take an active role in remembering and reimagining for ourselves events we’d rather forget. This article will describe both Spiegelman’s art and Kosakowski’s film. It will show that it is by deleting the towers that both these artists manage to rethink the meaning and symbolic dimension of the 9/11 events.